Identifying the Presence of Anxiety in Heart Failure Patients - Nurhayati, Nurhayati; Andari, Fatsiwi Nunik; Fredrika, Larra (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Heart failure is an emerging disease associated with morbidity and mortality. The prevalence of heart failure is expected to expand largely due to population aging and rising risk factors of heart failure incidence.Purpose: To examine the presence of anxiety and its contributing factors among heart failure patientsMethods: A descriptive cross-sectional study was performed at a cardiovascular outpatient of a public hospital in Indonesia. The Zung Self-rating Anxiety Scale (SAS) was used to determine the anxiety level of respondents.Results: Thirty heart failure outpatients enrolled in this study, 76.7% were male with the mean age of 50.0 years (SD 12.8). Regarding the SAS score, 60% of respondents experienced anxiety. Age, gender, educational level, NYHA classification, comorbidities, and body mass index were associated with the presence of anxiety.Conclusions: This study indicated that coexisting anxiety was found in heart failure patients. The intervention on anxiety which focuses on individuals might be needed to improve health and decrease the anxiety level.